The Influence of the Work Environment on the Performance of Employees in the Production Division at PT. XYZ - Yunus Agustinus; Yudi Kristanto; Setiawati Setiawati (Business Management, 2025)
This research is motivated by the declining performance of PT. XYZ employees which can be caused by several factors. Factors that influence performance include the work environment. The phenomena that occur include declining employee performance. The objectives of this research are: 1. To determine the Work Environment at PT. XYZ, 2. To determine the Employee Performance at PT United Steel Center Indonesia, 3. To determine whether or not the Work Environment has an influence on Employee Performance at PT. XYZ. This research, which uses a quantitative method with an associative technique, was conducted at PT. XYZ with a population of 86 employees with a data collection technique using a questionnaire. Based on the results of the research conducted, the results of the multiple linear regression equation test  can be used to explain the form of a linear relationship between the Work Environment and Employee Performance. The simple linear regression equation  shows that if the Work Environment and Employee Performance are measured using the instrument used in this study, then every increase of one unit in the Work Environment score (X) will be followed by an increase in the Employee Performance score of 0.905 with a constant of .